The Influence of Work Ability and Dicipline Employee to Quality of Service Vehicle Tax Payment (PKB) in SAMSAT Semarang Units III - Dini Sudiyati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2012)
As a public service providers, SAMSAT Semarang Units III is still not optimal in carrying out payment services the Vehicle Tax (PKB). In this study the authors examined the quality of payment services the Vehicle Tax (PKB) in SAMSAT Semarang Units III to determine whether there is influence between the factors of work ability and discipline of employees for payment of service quality of the Vehicle Tax (PKB).Type of study is a research type ekspalanatori. This study used a sample of 40 respondents to the selection of accidental sampling technique. Analysis of data using quantitative methods. Testing the hypothesis using Rank Correlation Coefficient formula and formula Kendall Coefficient of Concordance.According to the results showed a significant relationship between work ability variables (X1) with the quality of service (Y) with great effect by 25.50%, a significant relationship between the discipline variable (X2) with the quality of service (Y) with the major influence of 16.24%, and significant relationship between work ability (X1) and discipline (X2) on the quality of service (Y) with 52.42% of the effect. Based on the results showed that the work ability and labor discipline an employee has a relationship with the quality of the Vehicle Tax payments (PKB) in SAMSAT Semarang Units III.